European Funds and the Evaluation of Their Application in the Northern Great Plain Region - Nagy, János Attila (Acta Agraria Debreceniensis, 2005)
Presently, the process of regionalization is slowly progressing in Hungary. The regional institutional system is young and the institutional experiences are limited. The Hungarian regional development agencies are operated with a limited number of personnel and their budget is only a fraction of EU regional agencies of similar size. There is no unequivocal cooperation between regional development agencies and county development agencies. In the absence of these, the strategical objectives of the region cannot be aligned and the application of consistent development policies cannot be achieved. In the past five-six years the supports from EU Pre-Accession Funds, along with the new tools of regional development policies, have all contributed to the development of the North Great Plain Region. Phare projects – beside supporting development – have played a significant role in forming the approach of individuals who are actively involved in regional development, in promoting cooperation among cross-border and other regions, as well as in preparing the regions to accept EU structural funds. Prior to the May 1st, 2004 EU accession of Hungary, the North Great Plain Region received 24-25% in direct regional development funds in the Nineties. The support per capita in the case of TFC, TEKI and CÉDE has exceeded the national average. The North Great Plain Region has received support from investment type agricultural supports, the Employment Fund and the Touristical Directives that well exceeded the national average, from the sectoral resource funds. However, the applicants of the North Great Plain Region have received little support in the case of environmental, water management and especially road development supports. About 200 applications have been submitted for the SAPARD calls nationally, 32 of these were from the North Great Plain Region. The significance of cooperation among sub-regions is demonstrated by the fact that, except for 15 settlements in Szabolcs-Szatmár-Bereg county, all have submitted an application. The efforts of inhabitants is highlighted by the high number of submitted applications, as well as by the significant degree of own contribution. Still, the GDP of the North Great Plain Region has not increased, the rate and tendency of unemployment does not sufficiently reflect the positive effect of supports. The Regional Development Directive has provided support for the development of many small- and medium size enterprises, but their effect did not ensure a sustained economic growth.The greatest difficulty is that the number of dedicated professionals who are skilled in regional politics and regional development is few. However, advantages of our EU accession can only be exploited if a group of highly skilled professionals is provided on local, county, regional and national level as well. Thus, we need a group of professionals who are informed about the European Union, the EU support forms and most of all about the operation of Structural Funds and Cohesion Funds to establish the suitable institutional background for professionally handling the funds obtained from the EU, to prepare the professional documents to access the funds and to generate development projects to efficiently use the funds as well as establishing connections with the institutions of the EU. Appropriate share from funds coming from the EU is only possible if the country, certain regions, counties and sub-regions can achieve rapid results in the areas listed above.